Post-Translational Modifications in Atopic Dermatitis: Current Research and Clinical Relevance - Ma, Xin; Ru, Yi; Luo, Ying; Kuai, Le; Chen, Qi-Long; Bai, Yun; Liu, Ye-Qiang; Chen, Jia; Luo, Yue; Song, Jian-Kun; Zhou, Mi; Li, Bin (Frontiers in Cell and Developmental Biology, 2022)
Atopic dermatitis (AD) is a chronic and relapsing cutaneous disorder characterized by compromised immune system, excessive inflammation, and skin barrier disruption. Post-translational modifications (PTMs) are covalent and enzymatic modifications of proteins after their translation, which have been reported to play roles in inflammatory and allergic diseases. However, less attention has been paid to the effect of PTMs on AD. This review summarized the knowledge of six major classes (including phosphorylation, acetylation, ubiquitination, SUMOylation, glycosylation, o-glycosylation, and glycation) of PTMs in AD pathogenesis and discussed the opportunities for disease management.